Cross-Cultural Perceptions of Business Ethics: Evidence from the United States and China - Gift, Michael Joseph 1949-; Gift, Paul; Zheng, Qinqin (2013)
A number of empirical studies have examined business ethics across cultures, focusing primarily on differences in ethical profiles between cultures and groups. When managers consider whether or not to develop a business relationship with those from a different culture, their decision may be affected by actual differences in ethical profiles, but potentially even more so by their perceptions of ethicality in the counterpart culture. The latter issue has been largely ignored in extant empirical research regarding cross-cultural ethical profiles. In this study, we employ a design that allows for a more complete analysis of cross-cultural perspectives, examining both the manner in which selected cultures view themselves and the manner in which those same cultures perceive the ethical profiles of others. To this end, we surveyed master’s students in business fields at several universities in the United States and China—two countries/cultures that engage in a significant amount of business transactions—and examined differences in personal ethical profiles across cultures, differences in one group’s ethical profile and the way it is perceived by the other group, and differences in perceived ethical profiles across cultures; that is, differences in how groups view each other. Findings suggest meaningful discrepancies in the ethical perceptions formed toward the counterpart culture. Results support a role for ethical perceptions in future research, and further examination and inquiry into the development and adaptation of ethical perceptions in cross-cultural business dealings.
Keywords: Survey instruments; International Business; Ethical vignettes; ethical perceptions; Cross-cultural perceptions; Business Ethics